2018
DOI: 10.1053/j.gastro.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Changing Trends in Etiology-Based Annual Mortality From Chronic Liver Disease, From 2007 Through 2016

Abstract: In our population-based analysis of chronic liver disease mortality in the United States, the decrease in HCV-related mortality coincided with the introduction of direct-acting antiviral therapies, whereas mortality from ALD and nonalcoholic fatty liver disease increased during the same period. Minorities in the United States have disproportionately higher mortality related to chronic liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
171
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(178 citation statements)
references
References 36 publications
5
171
1
1
Order By: Relevance
“…11,12 A study using the national US mortality database reported an increase in the mortality of NAFLD from an annual rate of 6.1% in 2007-2013 to 11.3% in 2013-2016. 13 Globally, liver-specific mortality among patients with NAFLD was 0.77 per 1000 person-years with an overall mortality of 15.44 per 1000 persons-years. 3 Given the current global landscape of NAFLD, concerted efforts to better understand the modifiable predictors of NAFLD globally and regionally are warranted to retard and hopefully reverse the currently rising rates of disease burden and increase in healthcare utilization.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…11,12 A study using the national US mortality database reported an increase in the mortality of NAFLD from an annual rate of 6.1% in 2007-2013 to 11.3% in 2013-2016. 13 Globally, liver-specific mortality among patients with NAFLD was 0.77 per 1000 person-years with an overall mortality of 15.44 per 1000 persons-years. 3 Given the current global landscape of NAFLD, concerted efforts to better understand the modifiable predictors of NAFLD globally and regionally are warranted to retard and hopefully reverse the currently rising rates of disease burden and increase in healthcare utilization.…”
Section: Introductionmentioning
confidence: 98%
“…Not surprisingly, NAFLD‐related advanced fibrosis is on the rise at an accelerated pace in American adults, which translates to an increase in overall and cause‐specific mortality . A study using the national US mortality database reported an increase in the mortality of NAFLD from an annual rate of 6.1% in 2007‐2013 to 11.3% in 2013‐2016 . Globally, liver‐specific mortality among patients with NAFLD was 0.77 per 1000 person‐years with an overall mortality of 15.44 per 1000 persons‐years .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Not surprisingly, a recent study showed that NAFLD-related advanced fibrosis is on the rise at an accelerated pace in American adults, 3 which may result in increased overall mortality and cause-specific death. 6 These are particularly ominous trends, especially in the absence of approved pharmacologic therapy for NAFLD. 6 These are particularly ominous trends, especially in the absence of approved pharmacologic therapy for NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…NAFLD includes simple steatosis (SS) and nonalcoholic steatohepatitis (NASH), which may advance to cirrhosis and hepatocellular carcinoma (HCC) . NAFLD‐related mortality, attributing to hepatic diseases (ie, cirrhosis, its complications, and HCC) and extra‐hepatic diseases (ie, chronic kidney disease, cardiovascular diseases [CVD], cerebrovascular disorders, and malignancies), continues to increase in contrast to decreasing trends in viral hepatitis‐related mortality . Nonetheless, the need for noninvasive diagnosis and treatment of NAFLD remain unmet …”
Section: Introductionmentioning
confidence: 99%